Synthesis of Fe/SiO2 and iron oxides/SiO2 nanocomposites by long-term ball milling - Pozo Lopez, Gabriela del Valle (2014)
Iron oxide/SiO2 nanocomposites are synthesized by dry ball-milling a mixture of bcc Fe and α-quartz powders for prolonged times. A sequence of nanocomposites is obtained, with small magnetic particles dispersed in a non magnetic, amorphous matrix. The powders are characterized by X-ray diffraction and transmission electron microscopy. The magnetic hysteresis properties are investigated in the range 50-300 K. After 120 h milling, deformed, non-spherical, α-Fe nanocrystallites of about 10 nm in size and very few small (<10 nm) maghemite particles are found. At room temperature, iron particles are ferromagnetic and a large effective magnetic anisotropy is estimated, which is mainly attributed to surface effects. Between 160 and 200 h milling, maghemite nanoparticles are observed while after 220 h grinding, hematite phase appears; after 340 h milling, the sample consists of ferromagnetic hematite particles with a broad size distribution (5-50 nm) embedded in an amorphous matrix.